Determinación de plomo en raíces de Manihot esculenta (yuca) en el distrito de campo verde, Ucayali - Perú - Marin Cueva, Claudia Mercedes (2023)
The present study aimed of determine the levels of lead (Pb) in the edible root of cassava (Manihot esculenta) in the district of Campo Verde Ucayali – Peru. The research was non-experimental and descriptive, with the study population consisting of all agricultural plots located in the Campo Verde District. Intentional non-probabilistic sampling was applied, and 500 g of roots from 10 cassava clones were analyzed after being dried at 70°C for 48 hours. Once crushed, a 4:1 perchloric nitric solution was applied for 24 hours, and the roots were later digested using the EPA 3050 method. Finally, the total Pb content was determined by wet method in an atomic absorption spectrophotometer. The study found significant differences between the Pb averages of the cassava roots of the evaluated clones. The clones NB231, IM362-SF and AA063 accumulated the highest amount of Pb, while the clones NAL252, IM361-SF, MC015, CN025, SC062, KM44004 accumulated lower amounts. The values found showed that all cassava clones (Manihot esculenta) accumulated Pb concentrations higher than the máximum permisible limits established by the Codex Alimentarius. This could cause health problems for consumers.